Eksplikasi Mediasi Terhadap Perkara Perceraian - Muh. Syafwan Sikri; Kairuddin Karim; Muhammad Akbar Fhad Syahril (Jurnal Litigasi Amsir, 2022)
Mediation is a method of resolving disputes through a negotiation process to obtain an agreement between the Parties with the assistance of a Mediator. This study aims to determine and understand the effectiveness of mediation on the settlement of divorce cases at the Religious Courts of Sidenreng Rappang Regency and to find out and understand the form and process of mediators regarding Divorce at the Religious Courts of Sidenreng Rappang Regency. This study uses normative and empirical research. The results show that the implementation of mediation in divorce cases at the Religious Court of Sidendereng Rappang does not work effectively due to several factors. The factors that hinder the divorce mediation process at the Religious Court of Sidenreng Rappang Regency include the legal culture of the people who have litigations at the Sidenreng Rappang Religious Court, and the lack of understanding of the court as a place to seek justice, and the low culture of the community to make peace.